3D transient elasto-plastic finite element analysis of a flatted railway wheel in rolling contact. Issue 6 (2nd November 2018) - Otorabad, Hossein Alizadeh; Tehrani, Parisa Hosseini; Younesian, Davood
ABSTRACT: A precise study of stress state is crucial for an accurate evaluation of railway wheel defects. Wheel flats cause severe impact loads, which aggravate wheel failure. This paper describes 3D transient elasto-plastic finite element analyses of undamaged and flatted railway wheels using Chaboche's plasticity model as material model. The effect of the impact load is considered on contact region parameters that influence the stress. The results show that in a flatted wheel, the maximum contact force might not lead to a maximum von-Mises stress. It occurs in all cases considered, in a cross-section just above the leading edge of the wheel flat.